The effect of platelet-rich plasma on cavernous nerve regeneration in a rat model - Xiegang Ding; Shiwen Li; Xinmin Zheng; Li‐Quan Hu; Wanli Hu; Yi Luo (2009)
The aim of this study was to investigate the effect of platelet-rich plasma (PRP) on cavernous nerve (CN) regeneration and functional status in a nerve-crush rat model.Twenty-four Sprague-Dawley male rats were randomly divided into three equal groups: eight had a sham operation, eight underwent bilateral nerve crushing with no further intervention and eight underwent bilateral nerve crushing with an immediate application of PRP on the site of injury.Erectile function was assessed by CN electrostimulation at 3 months and nerve regeneration was assessed by toluidine blue staining of CN and nicotinamide adenine dinucleotide phosphate (NADPH)-diaphorase staining of penile tissue.Three months after surgery, in the group that underwent bilateral nerve crushing with no further intervention, the functional evaluation showed a lower mean maximal intracavernous pressure (ICP) and maximal ICP per mean arterial pressure (MAP) with CN stimulation than those in the sham group.In the group with an immediate application of PRP, the mean maximal ICP and maximal ICP/MAP were significantly higher than those in the injured control group.Histologically, the group with the application of PRP had more myelinated axons of CNs and more NADPH-diaphorase-positive nerve fibres than the injured control group but fewer than the sham group.These results show that the application of PRP to the site of CN-crush injury facilitates nerve regeneration and recovery of erectile function.Our research indicates that clinical application of PRP has potential repairing effect on CN and peripheral nerves.